Field reports form, contributed by Robert Cecil, fall 1986 - Cecil, Robert I.et al (1986)
Field notes of bird sightings by Cecil and others, primarily in southeastern Iowa. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly Report of fall 1986. Epson - sheet feed